2018
DOI: 10.1159/000489751
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic Acid-Mediated Sonodynamic Therapy Alleviates Atherosclerosis via Enhancing Efferocytosis and Facilitating a Shift in the Th1/Th2 Balance Toward Th2 Polarization

Abstract: Background/Aims: We and other groups have demonstrated that 5-aminolevulinic acid (ALA)-mediated sonodynamic therapy (ALA-SDT) induces macrophage and foam cell apoptosis and stabilizes atherosclerosis (AS) plaques in animal models. Lymphocytes also play vital roles in the development of AS. The primary purpose of the present study was to investigate the effects of ALA-SDT on T helper (Th) cell fate and function, Th subset differentiation, and atherosclerotic lesion stability. Methods: We utilized ALA-SDT on We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…65 However, the role of the Th2 immune response in atherosclerosis has been controversial. 66 While some studies report a protective effect, 67,68 others have demonstrated a pro-atherogenic impact. [69][70][71] Of note, increased expression of CCL17 and CCL22 has been found in atherosclerotic lesions, with one study suggesting the role of CCL17 in driving atherosclerosis via restraining regulatory T-cell homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…65 However, the role of the Th2 immune response in atherosclerosis has been controversial. 66 While some studies report a protective effect, 67,68 others have demonstrated a pro-atherogenic impact. [69][70][71] Of note, increased expression of CCL17 and CCL22 has been found in atherosclerotic lesions, with one study suggesting the role of CCL17 in driving atherosclerosis via restraining regulatory T-cell homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…e decrease in AS is related to the decrease in the 1/ 2 ratio [36]. e 1/ 2 balance may be targeted in AS prevention and treatment research [37]. Our research first found that the ARCR herb pair slowed the development of AS in ApoE-/-mice, stabilized plaques, and regulated the balance of serum inflammatory factors.…”
Section: Discussionmentioning
confidence: 67%
“…The implications of Th2 cells are more ambiguous, as they have been involved in AS resistance, but at times have also shown a slight atherosclerogenic effect. By contrast, regulatory T cells reduce the formation of AS and play a protective role (34)(35)(36)(37)(38)(39). The co-stimulatory molecules involved in immune synapses between T cells and APCs can regulate 16) rats; nuclei were counterstained with DAPI.…”
Section: Discussionmentioning
confidence: 99%